Chitosan-Nanoparticles As A Drug Delivery System For 5-Fluorouracil - Suardi, Muslim (2003)
In order to formulate chitosan nanoparticles, the influence of chitosan concentrations, type and concentration of emulsifiers, type of acid, concentration of acetic acid, and mixing method were investigated. The results showed that the size of nanoparticles was directly correlated to the chitosan concentration but inversely associated with emulsifier concentrations.